P206 Prevalence and risk factors associated with chlamydia trachomatis (CT), mycoplasma genitalium (MG) and neisseria gonorrhoeae(NG): cross-sectional study in three sexual health clinics. (8th June 2017) - Broad, Claire; Harding-Esch, Emma; Harrison, Mark; Pond, Marcus; Tan, NgeeKeong; Soares, Clare; Fuller, Sebastian; Okala, Sandra; Sadiq, Syed Tariq
Abstract : Introduction: Chlamydia trachomatis (CT), Mycoplasma genitalium (MG), and Neisseria gonorrhoeae (NG) infections contribute to major reproductive health sequelae. CT and NG are routinely tested for in sexual health clinics (SHCs), whereas MG is not. Population prevalence estimates for males and females for CT and MG are >1% and <0.1% for NG infection. Risk factor data, which help target control interventions, are limited in men-who-have-sex-with-men (MSM). We assessed prevalence and risk factor data in symptomatic patients accessing SHCs. Methods: Patients aged ≥16 years with symptoms of an STI provided: vulvovaginal swabs (females), first void urine (men-who-have-sex-with-women (MSW) and MSM) and pharyngeal and rectal swabs (MSM). Routine clinic results were obtained and FTD Urethritis Plus kit used to detect MG. Risk factors (RFs) were analysed using univariate (UV) and multivariate (MV) logistic regression. Results: The only RFs associated with any organism in MV analyses was in females. Being aged 16–19, a contact of someone with an STI, and not bleeding were associated with CT and being a contact was the only RF for NG. Discussion: CT and MG positivity were highest in MSW compared with other patient groups, whereas NG positivity was highest in MSM, especially rectal samples. In the absence of routine MG testing, NG-positive MSM would be treated with 1 g azithromycin, (combined with 500 mg ceftriaxone) which could result in MG antimicrobial resistance development. From our study population, with no RFs for CT, NG or MG, a targeted test and treat approach would not be beneficial in MSW or MSM.